2019
DOI: 10.14735/amko2019s36
|View full text |Cite
|
Sign up to set email alerts
|

Germline CHEK2 Gene Mutations in Hereditary Breast Cancer Predisposition – Mutation Types and their Biological and Clinical Relevance

Abstract: Východiska: Dědičné mutace v genu CHEK2 kódujícím CHK2 proteinkinázu způsobují středně zvýšené riziko vzniku karcinomu prsu (breast cancer-BC) a dalších nádorových onemocnění. Vysoká populační variabilita CHEK2 mutací a výskyt vzácných missense variant nejasného významu (variants of unknown clinical significance-VUS) komplikuje odhad rizika vzniku nádorových onemocnění u nosičů germinálních variant. Soubor pacientů a metody: Mutační analýzu CHEK2, vč. analýzy velkých přestaveb, jsme provedli u 1 526 vysoce riz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Despite the relatively high prevalence of this variant in the Polish population (in the north of Slovakia) (4.8-5.2%)[57,63], more recent studies did not confirm its pathogenic role in the Polish population of breast cancer patients[63] nor in patients with ovarian cancer[64]. According to the data from the Czech Republic, the frequency of this variant in the patient cohort was 3.08% (47 out of 1,523) compare to the frequency of 3.1% in controls (104 out of 3,360)[65]. However, Lerner Ellis et al[40] reported 17 cases of the mentioned CHEK2 variant in the large study of 3,251 HBOC patients from Ontario region, which represents only 0.5%.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the relatively high prevalence of this variant in the Polish population (in the north of Slovakia) (4.8-5.2%)[57,63], more recent studies did not confirm its pathogenic role in the Polish population of breast cancer patients[63] nor in patients with ovarian cancer[64]. According to the data from the Czech Republic, the frequency of this variant in the patient cohort was 3.08% (47 out of 1,523) compare to the frequency of 3.1% in controls (104 out of 3,360)[65]. However, Lerner Ellis et al[40] reported 17 cases of the mentioned CHEK2 variant in the large study of 3,251 HBOC patients from Ontario region, which represents only 0.5%.…”
mentioning
confidence: 96%
“…These data are certainly influenced by a low number of samples. However, they indicate that:1./ This is additional evidence suggesting that the controversial CHEK2 variant c.599T>C (p.Ile200Thr) represents with high probability a low penetrance variant associated with lower susceptibility of cancer risk[62] mainly because it is known that CHEK2 protein affected by this missense variant has a lower activity[65].2./ The presence of pathogenic mutations in HBOC-associated genes relates to the notable decrease of the age of cancer diagnosis and this fact results in a significant increase of mutation frequency with decreasing age at diagnosis[69].Overall, the age at cancer diagnosis in our study is relatively low when comparing with other multigene based studies. For example, Foglietta et al[47] reported the mean age in the group of breast cancer cases to be 46 years and in the BRCA1/2 positive cases even higher at 48 years, while the mean age in our group of breast cancer patients was 43.7 and in positive cases at 43.5.…”
mentioning
confidence: 99%